Improving Shoe Product Quality Through the New Seven Tools Approach and Failure Mode Effect Analysis (FMEA): Perbaikan Kualitas Pada Produk Sepatu Melalui Pendekatan New Seven Tools Dan Failure Mode Effect Analysis (FMEA) - Subono, Muhammad Wibbie Wiweka; Rochmoeljati, Rr. (Indonesian Journal of Innovation Studies, 2026)
General Background: Quality control is essential for ensuring competitiveness in manufacturing industries, particularly in footwear production. Specific Background: UD. XYZ experiences a defect rate of 12.85%, exceeding the company standard of 5%, indicating systemic issues in its production process. Knowledge Gap: Previous studies have utilized New Seven Tools and FMEA, yet have not sufficiently integrated both methods to produce comprehensive improvement recommendations tailored to the root causes of shoe defects. Aim: This study aims to identify defect-causing factors and propose corrective actions using combined New Seven Tools and Failure Mode and Effect Analysis (FMEA). Results: Analysis revealed 27 proposed improvements through the PDPC, with 25 deemed feasible, while FMEA identified untidy sewing as the most critical failure mode, with the highest RPN value of 336. Novelty: This study offers an integrated diagnostic–corrective framework that systematically links qualitative mapping tools with quantitative risk prioritization to strengthen quality improvement strategies. Implications: Findings provide actionable guidance for enhancing worker performance, machine calibration, material handling, and production methods, supporting sustained quality enhancement in the footwear industry. Highlights: Identifies key defect sources in shoe production using integrated qualitative and quantitative methods. Highlights untidy sewing as the most critical issue based on the highest RPN value (336). Provides feasible improvement actions, with 25 of 27 recommendations implementable for quality enhancement. Keywords: Quality Control, New Seven Tools, FMEA, Shoe Manufacturing, Defect Reduction